2012
DOI: 10.3109/10428194.2012.753446
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intensive care unit admission is associated with increased mortality in patients with cancer with acute respiratory failure

Abstract: Acute respiratory failure (ARF) is the leading reason for intensive care unit (ICU) admission in patients with cancer. The aim of this study was to identify early predictors of death in patients with cancer admitted to the ICU for ARF who were not intubated at admission. We conducted analysis of a prospective randomized controlled trial including 219 patients with cancer with ARF in which day-28 mortality was a secondary endpoint. Mortality at day 28 was 31.1%. By multivariate analysis, independent predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 31 publications
4
98
0
7
Order By: Relevance
“…Only close collaboration among hematologists, intensivists, and other specialists can meet these requirements [12]. The diagnosis and treatment of acute respiratory failure has been the most controversial issue over the past two decades [13][14][15]. Research fueled by this controversy has resulted in a sharp drop in mortality, from nearly 100% to about 40% [16].…”
Section: Introductionmentioning
confidence: 96%
“…Only close collaboration among hematologists, intensivists, and other specialists can meet these requirements [12]. The diagnosis and treatment of acute respiratory failure has been the most controversial issue over the past two decades [13][14][15]. Research fueled by this controversy has resulted in a sharp drop in mortality, from nearly 100% to about 40% [16].…”
Section: Introductionmentioning
confidence: 96%
“…An early ICU management may translate into better survival, allowing the use of noninvasive diagnostic strategies, 90,91 reducing the number of patients admitted with MOF and initiating early organ failure support. Five recent studies demonstrated the benefit of early ICU admission in the context of cancer patients with ARF, 89 newly diagnosed AML, 92 septic shock of pulmonary origin, 93 cancer patients admitted to the ICU 94 and for patients with hematologic malignancies admitted to the ICU. 10 Yet, it has never been clearly demonstrated in allo-HSCT patients.…”
Section: Icu Management Improvementsmentioning
confidence: 99%
“…The finding that patients with multiple organ dysfunction and high organ failure scores at ICU admission have higher mortality rates has generated several hypotheses regarding the possible link between delayed ICU admission and mortality. 89 High acute illness severity at ICU admission can be explained by different factors, mainly represented by diagnostic difficulties and suboptimal evaluation in wards, resulting in underestimation of disease severity followed by an unexpected clinical deterioration. An early ICU management may translate into better survival, allowing the use of noninvasive diagnostic strategies, 90,91 reducing the number of patients admitted with MOF and initiating early organ failure support.…”
Section: Icu Management Improvementsmentioning
confidence: 99%
“…Increased attention, observation, and therapeutics substantially improve the probability of survival in deteriorating patients 28 ; delay of such interventions for patients developing acute respiratory failure increases the chances of death. 29 On the other hand, most interventions (eg, aggressive respiratory secretion clearance 30 ) require additional resources that are not feasible to provide to the majority of in-patients. It may not be straightforward to determine which patients are in sufficient jeopardy to warrant resource-intensive interventions.…”
Section: The Current Challenge Of Respiratory Compromisementioning
confidence: 99%